Mechanistic modelling of time-dependent fatigue crack growth in Ni-based superalloys. (28th June 2016) - Chan, Kwai S.
Abstract : Advanced Ni-based superalloys for aero-engine disk applications can experience multiple damage mechanisms that include oxidation, creep and stress corrosion in additional to cycle-dependent fatigue crack initiation and growth. Interactions of these various damage mechanisms can lead to the occurrence of frequency, temperature, heat dwell and environmental effects on the fatigue crack growth response and service life of Ni-based superalloys. In this overview paper, the development of a set of generic microstructure-based fatigue crack growth models for treating concurrent time-dependent and cycle-dependent damage mechanisms at the microstructural levels is summarised. Key features of the mechanistic models are highlighted and utilised to assess the variability of time-dependent fatigue crack growth response in the threshold and power-law regimes due to variations in microstructure such as grain size, and γ′ size. This methodology provides a pathway for evaluating microstructural effects on multiple damage modes and extending the service lives of hot-section components.